PENGARUH PRODUK DOMESTIK DAERAH BRUTO, PENDUDUK, DAN PENANGGURANGAN TERHADAP KEMISKINAN DI KALIMANTAN SELATAN - Surti Surti; Setyo Tri Wahyudi; Lutfi Asnan Qodri; Syahrial Shaddiq (Bilancia : Jurnal Ilmiah Akuntansi, 2023)
ABSTRACT Poverty is a problem faced by almost all developing countries, there is no problem in Indonesia. South Kalimantan is one of the provinces in South Kalimantan with the third-smallest population; this problem is not a concern. The problem of the number of poor people in 13 districts/cities is the main problem faced by South Kalimantan. The poverty that occurs is the result of a large population, such as Banjarmasin with the largest population also has the highest number of poor people among other districts/cities in South Kalimantan. The sticky rice of residents in the capital city and surrounding cities has resulted in the inability of employment opportunities to absorb work as a whole, resulting in an effect that returns to Banjarmasin. This unemployment will work on the inability to earn income to meet the needs of life and face poverty. Policies related to leading sectors also need to be considered where the economic sector that should be spurred into a leading sector is the sector with the largest employment absorption and the sector that has links with the sector so that the majority of the population of South Kalimantan can increase. The results of the analysis state that except for gross regional domestic product (GRDP), population and unemployment have a significant individual effect on poverty. However, simultaneously the three independent variables affect poverty. The data was analyzed using the Least Square Panel using data on poverty, population, unemployment, and GRDP of 13 cities/districts in South Kalimantan from 2016 to 2020. Keywords: Poverty, GRDP, Population, Unemployment, South Kalimantan ABSTRAK Kemiskinan merupakan masalah yang dihadapi oleh hampir semua negara berkembang, tidak ada masalah di Indonesia. Kalimantan Selatan merupakan salah satu provinsi di Kalimantan Selatan dengan jumlah penduduk terkecil ketiga; masalah ini tidak menjadi perhatian. Permasalahan jumlah penduduk miskin di 13 kabupaten/kota menjadi permasalahan utama yang dihadapi Kalimantan Selatan. Kemiskinan yang terjadi diakibatkan oleh jumlah penduduk yang besar, seperti Banjarmasin dengan jumlah penduduk terbesar juga mempunyai jumlah penduduk miskin terbanyak diantara kabupaten/kota lain di Kalimantan Selatan. Ketan yang dialami warga ibu kota dan sekitarnya mengakibatkan tidak mampunya lapangan kerja dalam menyerap lapangan kerja secara menyeluruh sehingga berdampak kembali ke Banjarmasin. Pengangguran ini akan berdampak pada ketidakmampuan memperoleh penghasilan untuk memenuhi kebutuhan hidup dan menghadapi kemiskinan. Kebijakan terkait sektor unggulan juga perlu diperhatikan dimana sektor perekonomian yang patut dipacu menjadi sektor unggulan adalah sektor dengan penyerapan tenaga kerja terbesar dan sektor yang mempunyai keterkaitan dengan sektor tersebut sehingga mayoritas penduduk Kalsel dapat meningkatkan. Hasil analisis menyatakan bahwa selain produk domestik regional bruto (PDRB), jumlah penduduk dan pengangguran mempunyai pengaruh individual yang signifikan terhadap kemiskinan. Namun secara simultan ketiga variabel independen tersebut mempengaruhi kemiskinan. Data dianalisis menggunakan Least Square Panel dengan menggunakan data kemiskinan, jumlah penduduk, pengangguran, dan PDRB 13 kota/kabupaten di Kalimantan Selatan pada tahun 2016 hingga 2020. Kata Kunci: Kemiskinan, PDRB, Jumlah Penduduk, Pengangguran, Kalimantan Selatan